2020
DOI: 10.3389/fvets.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogenic Leptospira Species in the Urogenital Tract of Water Buffaloes (Bubalus bubalis) From the Amazon River Delta Region, Brazil

Abstract: In the current context of deforestation and fire in the Amazon, buffaloes could be a cost-effective and sustainable alternative for cattle production in the region, as they can convert low-quality foods and be raised in floodplain areas. However, little is known about the reproductive diseases that affect these animals; thus, the purpose of this study was to perform the molecular characterization of Leptospira spp. in the urogenital tract of water buffaloes (Bubalus bubalis) raised in the Amazon River Delta re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(46 reference statements)
0
3
0
1
Order By: Relevance
“…The high prevalence found in this study shows that leptospirosis is present in infecting buffaloes in the state of Paraná and may be related to management, environmental conditions, herd health status, lack of vaccination and routine diagnosis or control, and failure to treat or dispose of seropositive animals (Higino et al 2012). This demands attention regarding public health since these animals are used as a source of meat or milk and have contact with humans (Guedes et al 2020a).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The high prevalence found in this study shows that leptospirosis is present in infecting buffaloes in the state of Paraná and may be related to management, environmental conditions, herd health status, lack of vaccination and routine diagnosis or control, and failure to treat or dispose of seropositive animals (Higino et al 2012). This demands attention regarding public health since these animals are used as a source of meat or milk and have contact with humans (Guedes et al 2020a).…”
Section: Discussionmentioning
confidence: 85%
“…Leptospirosis in buffaloes has been reported in several countries through serological studies that demonstrated different prevalences (Konrad et al 2013, Alamuri et al 2019, Olmo et al 2019, Guedes et al 2020a). The frequency of leptospirosis in buffaloes in the state of Paraná found in the present study was 77.17% (213/276), a high result close to the 80% (164/205) found by Viana et al (2009) in Pará and 70.58% (216/306) found by Carvalho et al (2015) in Maranhão.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se conoce parcialmente la patogenia de la leptospirosis en B. bubalis, sin embargo, es probable que se produzcan problemas reproductivos similares a los vacunos, como abortos, infertilidad y disminución de la producción láctea [6,10]. La susceptibilidad a la infección también es dependiente de la edad, encontrándose más animales positivos a la prueba serológica estándar de aglutinación microscópica (MAT) en animales adultos [4,25].…”
Section: Introductionunclassified